Molecular and Biological Characterization of Two Very Virulent Infectious Bursal Disease Virus Isolates, Upm94/273 and Upm97/61 - Kong, Lih Ling (2003)
An atypical very virulent (w) strain (UPM94/273) and typical vv strain (UPM97/61) of infectious bursal disease virus (IBOV) isolated in Malaysia, were characterized both in vivo and at the molecular level. Comparison of the deduced amino acid sequences with other serotype 1 and 2 sequences revealed 16 amino acid residues, which were conserved only in the vvIBDV. Among the 16 unique amino acid differences, 8 were in VP1 (146 Asp, 147 Asn, 242 Glu, 390 Met, 393 Asp, 562 Pro, 687 Pro and 695 Arg), 3 were in VP2 (222 Ala, 256 lie and 294 lie), 2 were in VP3 (990 Val and 1005 Ala) and 3 were in VP4 (685 Asn, 715 Ser and 751 Asp). The importance of these unique amino acid residues is not known but they could affect the virulence of vvIBOV. The UPM94/273 also demonstrated 6 unique amino acid residues at segment A at positions Ser254, Glu270, Lys588, Ser745, Phe838 and Lys863 and 8 unique amino acid residues at segment B at positions Ala92, Ser100, Va1208, Asp253, Asp560, Asn565, Gly750 and Gly876. In addition, these amino acid substitutions have not been reported before in vvlBDV and were found only on variant, classical and/or serotype 2 strains. However, the VP5 region of both vvlBDV strains was conserved. The UPM97/6 1 demonstrated 7 unique amino acid substitutions at segment A and 4 unique amino acid substitutions at segment B. However, none of the amino acids changes have been reported elsewhere in other IBDV strains. Although the actual functions of the amino acid substitutions are not know, the unusual amino acid substitutions at segment A and/or B of both isolates may be important in virus virulence. Alignments of the nucleic acid and amino acid sequences of segment A and B followed by distance analysis allowed the generation of phylogenetic trees. Phylogenetic analysis based on segment A and B revealed that all the vvlBDV strains including U PM94/273 isolate can be clustered in a group that is distinct from classical, variant, attenuated and serotype 2 strains. However, the tree branching patterns were quite different between segment A and segment B. In addition, the vvlBDV strains showed several conserved amino acid substitutions at segment B as found in the Australian 002-73 and serotype 2 strains. These findings indicate that probably a genetic reassortment may have play an important role in the emergence of vvIBDV. Flow cytometry and real time peR assays, indicated that chickens infected with UPM97/61 induced higher percentages of apoptotic cells but lower level of viral load whereas UPM94/273 induced lower percentages of apoptotic cells but higher level of viral load, suggesting a negative correlation between viral load and apoptosis. These results indicated that U PM97/61 was more virulent than UPM94/273.